The Development of Psychological Capacity for Action: The Empowering Effect of a Microfinance Programme on Women in Sri Lanka. (September 2015) - Hansen, Nina; Stroebe, Katherine; de Lemus, Soledad
<x xml:space="preserve">Abstract</x> This work examines the effect of a microfinance intervention on psychological empowerment among women in the North of Sri Lanka. Psychological empowerment is defined as personal (personal control beliefs) and social (social networks) capacity for action. The intervention included relevant skills training, saving acti‐vities, and micro loans to eligible clients. In total, 88 women who had participated in the program for 12–18 months were randomly selected and compared with a matched control group (n = 84). As expected, women in the intervention group showed higher levels of personal control beliefs and reported a larger social network (indicators for personal and social capacity for action, respectively), compared to the control group. Importantly, women who received training showed stronger effects than women who did not, illustrating the importance of training to capacitate women. Implications for theory and practice of microfinance interventions designed to foster societal change toward gender equality are discussed.